Sjukvårdsmaterielkrisen 2019 - Jansson,Johan (2020)
From the first of October 2019 there was a new supplier of medical equipment in five regions in Sweden. From the second of October we had a medical equipment crisis on our hands. This thesis aims to uncover why one out of five regions was practically unharmed by the supply shortage and if this was due to active measurements taken by the region authorities or something else. The study uses Lundquist’s implementation theory in order to answer the research question: Why did one region manage to avoid the medical equipment crisis in 2019 and what were the main reasons for that outcome? The following conclusion was reached: By making smart priorities at the right time, to a fairly low cost, one region manage to stay above the crisis due to an active priority to maintain an two week extra supply storage that generated a minimum of extra cost but all the difference in a situation of supplier change.
Keywords: sjukvårdsmaterielkrisen 2019; försörjning; sjukvårdsmateriel; förvaltningsteori; krisberedskap